PERTANGGUNGJAWABAN PEMILIK USAHA TERHADAP KONSUMEN YANG MENGALAMI KERUGIAN AKIBAT PEMASANGAN EYELASH EXTENTION DI BY YUKA EYELASH - Weda, Ayu Nanda Putri; Dewi, Ni Komang Ratih Kumala (Jurnal Hukum Mahasiswa, 2024)
Being beautiful is the desire of all women, having eyelash extensions can make it easier for women to shorten time when they are in a hurry, without having to use cosmetics to beautify and beautify their eyes so they become more confident. The large amount of interest in opening this business has made eyelash extension business actors compete fiercely to attract consumers, such as providing discount prices and providing friendly service. However, the use of eyelash extensions causes side effects so that consumers feel disadvantaged. This study was carried out to determine the position of the agreement regarding the installation of eyelash extensions at By Yuka Eyelash and legal protection for consumers as well as the liability of the salon. This research uses empirical research methods with a factual and sociological approach. Based on the results of this research, By Yuka Eyelash provides responsibility for losses experienced by consumers due to the installation of eyelash extensions in the form of re-installation, providing a guarantee, providing compensation in the form of a refund.